Anykščių šnektos pokyčiai - Markevičienė, Žaneta (Kalbotyra, 2004)
All the descriptions and published texts of the Anykščiai local dialect (starting with the poem “Anykščių šilelis” (The Anykščiai Pinewood) by A. Baranauskas published in 1882 and finishing with works by Z. Zinkevičius) indicate that the Anykščiai local dialect belongs to North Anykštėnai. On the other hand, the latest audio recordings show that the southern variety of the dialect is increasingly becoming dominant in the town of Anykščiai and its surroundings. It is not separate features of the southern variety that are adopted in the said territories, but the entire system. Therefore, the Anykščiai local dialect sometimes has recurrence (flash-back) in its ongoing phonetic changes, e.g. the so-called žalininkai feature has been lost and regained again (stōraĩ nil stɔ.raĩ nil storы̇ ’(adv.) fat; thick’).